Contingency Management Banking: Reducing costs and increasing the efficacy of Contingency Management treatment for Substance Use Disorders (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Contingency Management (CM) is among the most effective behavioral interventions for cocaine use disorders (CUD), yet the dissemination of CM to community treatment settings has been limited and slow due partially to costs.Recently, our group completed the first Brazilian CM trial for CUD. Despite our positive results, we observed specific components of the CM procedure that could be contributing to unnecessary costs. Prompted by this experience and leveraging evidence-based behavioral science principles, we recently developed a modified version of CM designed to reduce costs and increase long-term engagement in treatment.In this technical article we present the scientific, clinical and practical rationale behind a novel CM procedure. We provide a detailed description and rationale for this procedure in an effort to stimulate discussion amongst other scientists about its utility across a diverse array of low-resource treatment settings and discuss why CM banking may reduce costs and enhance treatment engagement.
Keywords: Cocaine use disorders; Contingency Management; Psychosocial interventions; Crack; Cocaine; substance use disorders; treatment